Analytical techniques in biochemistry and molecular biology - Katoch, Rajan; SpringerLink (Online service). (New York Springer, 2011)
Long defined as a core subject in the life sciences, biochemistry now allows us to control living systems in ways undreamt of even a decade ago. Its relevance increases daily as plant biology and biotechnology move inexorably up the scientific agenda. This comprehensive volume explores the numerous experimental techniques that must be mastered by researchers in plant biology, biochemistry and biotechnology. As the interest in biochemical and molecular methods of investigating physiological processes rises, there's a concurrent development of new, faster, and more sensitive experimental procedures, allowing us to explore the inner workings of animal and plant organisms. Analytical Techniques in Biochemistry and Molecular Biology guides the reader through these methodologies, beginning with the preparation of solutions and the expression of their concentrates; continuing with the concept and preparation of buffers, a key element of working with enzymes; and discussing biochemical analysis, carbohydrates, and proteins and amino acids, as well as enzyme and isozyme analysis.  This volume also examines the full spectrum of protocols used in contemporary biochemical experimentation, including chromatographic separation procedures and the nutritional evaluation of foodstuffs. Lastly, the book covers cutting-edge techniques in biotechnology. Truly multidisciplinary, Analytical Techniques in Biochemistry and Molecular Biology is a valuable resource to researchers in biochemistry, biotechnology and their derivative fields
Preparation of solutions -- Expression of concentration -- Buffers and their preparation -- Techniques in biochemical evaluation -- Carbohydrate estimations -- Estimation of lipids -- Qualitative and quantitative estimations of amino acids and proteins -- Protein purification techniques -- Cell disruption and fractionation -- Enzymes in metabolism -- Isoenzyme analysis -- Chromatographic separations -- Methods for nutritional quality evaluation of food materials -- Nutritional evaluation of forages -- Techniques in molecular biology
Title from title screen (viewed September 25, 2023)
Electronic reproduction
Keywords: Biochemistry -- Experiments; Molecular biology -- Experiments; Molecular biology -- Technique